Creative Business Education Exploring the Contours of Pedagogical Praxis - Powell, Philip; Shankar Nayak, Bhabani (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This volume critically analyses the conceptual contours of pedagogical transformations in the field of creative business education. It calls for an integrated and ethnographic approach to understand, to analyse and to innovate creative curricula that is different from traditional business and management educations and its compliant culture. The book argues for a pluriversal vision based on social intelligence, critical thinking, inclusivity and creativity resulting in a holistic pedagogy that understands the social needs of people and of the planet. The critical reflections on everyday realities of life is central to this intercultural pedagogic approach to understanding and explaining different forms of contemporary crisis. The book brings together interdisciplinary academic practitioners and their praxis with different philosophical orientations within a single ethnographic and theoretical narrative to reclaim global citizenship rights in the age of artificial intelligence, democratic deficit, hyperreality and alienation. In this way, the volume breaks away from the narrow silo of disciplinary boundaries to outline the pedagogical praxis of creative and critical business education that challenges existing knowledge, power and institutions while offering alternative pedagogic approaches to learning, teaching and research. Bhabani Shankar Nayak is a political economist and works as Professor of Business Management and Programme Director of Strategic Business and Management at the University for the Creative Arts, UK. His research interests consist of closely interrelated and mutually guiding programmes surrounding political economy of religion, business, and capitalism, along with faith and globalisation, and economic policies. He is the author of Political Economy of Development and Business (2022), Modern Corporate Strategies at Work (2022), China: The Bankable State (2021), Disenchanted India and Beyond: Musings on the Lockdown Alternatives (2020), Hindu Fundamentalism and the Spirit of Global Capitalism in India (2018) and Nationalising Crisis: The Political Economy of Public Policy in India (2007). Philip Powell is Professor of Creative Business and Director of the Business School for the Creative Industries. Philip was previously Executive Dean, Pro Vice-Chancellor (Enterprise and Innovation), and Professor of Management at Birkbeck, University of London and Dean of the Faculty of Business, Law and Politics at the University of Hull. His research has resulted in over 350 published outputs in information systems, management, operations, and higher education management. He was Editor-in-Chief of the Information Systems Journal. He has served on a variety of public bodies concerned with skills development, enterprise and entrepreneurship and currently sits on the Institute for Apprenticeships Business and Management Route Panel.
1. Future of Creative Business Education -- 2. Towards Interculturality in International Creative Business and Management in Higher Education -- 3. The Meaning of Creativity Through the Ages: From Inspiration to Artificial Intelligence -- 4. The Global Citizen, Globalized Lifestyles and Pedagogy -- 5. Storytelling & Ethics: Understanding Ethical Storytelling for the Purpose of Business Education -- 6. 'My God I'm wearing Tesco!': Fashion, Pre-teen Femininity and the Commercialisation of Childhood -- 7. Inclusive Teaching Strategy in Creative Industry Education -- 8. Implications of Pedagogical Disassociation in U.K. Higher Education Business Schools: A Culturally Responsive Outlook -- 9. Understanding Trends of Collaboration and Creative Practice in the Fashion Industry: A Critical Approach Towards Curriculum Development in Higher Education -- 10. Student Voices: Journalism in Creative Education -- 11. Hyper-reality - A Dangerous Modern Phenomenon -- 12. Creative Tourism and Creative Tourists: A Review -- 13. Accelerated Times: Post-capitalism and Music Industry Pedagogy -- 14. Cultural and Creative Districts: A Literature Review and a Taxonomy -- 15. Innovation Through Engaged Learning: Working with Mode 2 Knowledge and Intrapreneurship -- 16. Professionalisation and Identification in UK Higher Arts Education -- 17. Interdisciplinary Limits of Creative Business Education.
Keywords: Executives-Training of; Management Education